2020
DOI: 10.3389/fphar.2020.01140
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of lncRNAs and Their Target Gene Signaling Pathways in Laryngeal Squamous Cell Carcinoma

Abstract: Laryngeal squamous cell carcinoma (LSCC) is a common malignant tumor that occurs in the head and neck. People living in areas with serious air pollution and those who smoke and drink for a long time belong to high-risk groups. Although great progress has been made in chemotherapy, radiotherapy, and molecular targeted therapy in recent years, the prognosis of patients is still not good. The proliferation, invasion, and apoptosis of LSCC are controlled by many factors, which are the key factors influencing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Therefore, our study identified LINC01291 as a tumor-promoting lncRNA in melanoma for the first time. lncRNAs are involved in carcinogenesis and cancer progression via a variety of different mechanisms [40]. At the transcriptional level, lncRNAs can epigenetically knockdown mRNAs [41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study identified LINC01291 as a tumor-promoting lncRNA in melanoma for the first time. lncRNAs are involved in carcinogenesis and cancer progression via a variety of different mechanisms [40]. At the transcriptional level, lncRNAs can epigenetically knockdown mRNAs [41].…”
Section: Discussionmentioning
confidence: 99%
“…Current treatments include surgery, radiotherapy. and chemotherapy, but the survival rate of cancer patients is still extremely low (64). The role of KLF4 in laryngeal cancer has been largely elusive.…”
Section: Laryngeal Carcinomamentioning
confidence: 99%
“… 9 lncRNAs can act tumor-promoting genes to promote the growth, invasion, and migration of cancer cells, or they can serve as tumor suppressor genes to inhibit head and neck tumor occurrence and development. 10 , 11 Various lncRNAs have different mechanisms and regulatory targets in the occurrence, development, and metastasis of head and neck tumors. lncRNAs can regulate gene transcription by binding to enzymes or protein complexes, can participate in chromosome remodeling and epigenetic regulation, and can also inhibit microRNA (miRNA) or alter mRNA modifications to regulate mRNA transcription and translation.…”
Section: Introductionmentioning
confidence: 99%